Regular assembly of cage siloxanes by hydrogen bonding of dimethylsilanol groups. Issue 55 (11th June 2015) - Sato, Naoto; Kuroda, Yoshiyuki; Abe, Takuya; Wada, Hiroaki; Shimojima, Atsushi; Kuroda, Kazuyuki
Abstract : A new class of ordered silica-based materials has been prepared by assembly of cage siloxanes with hydrogen bonds of dimethylsilanol groups at their corners. Abstract : A new class of ordered silica-based materials has been prepared by hydrogen bond-directed assembly of cage siloxanes modified with dimethylsilanol groups, providing a soft-chemical approach to crystalline silica materials with molecularly designed architectures.